Pengaruh Pelayanan, Transparansi Pengelolaan Dan Kepuasan Muzakki Terhadap Keputusan Memilih Unit Pengumpul Zakat (UPZ) Universitas Pamulang - Herlambang Herlambang; Danang Choirul Umam; Aerlangga Aerlangga (Prisani Cendekia, 2023)
This research aims to examine the influence of service quality, transparency of management, and muzakki satisfaction on the decision-making process in selecting the Zakat Collection Unit (UPZ) at Pamulang University. The study was conducted in March 2023, with a sample taken from the faculty members at Pamulang University who had become donors to the UPZ. A probability sampling approach was used with the simple random sampling technique, resulting in a sample size of 30 respondents. Data analysis was performed using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach. The sample size was determined based on the recommendation of Hair & Anderson (2014), which suggests a sample size of 5-10 times the number of indicators or parameters used in the model. The results of the analysis showed that service quality has a positive and significant influence on the decision-making process of the respondents. Study found that transparency of management did not have a significant influence on the decision-making process of the respondents. Muzakki satisfaction was also found to have no significant influence on the decision-making process.